Evaluation of applicability of DNA microarray–based characterization of bovine Shiga toxin–producing Escherichia coli isolates using whole genome sequence analysis. (September 2017) - Barth, Stefanie A.; Menge, Christian; Eichhorn, Inga; Semmler, Torsten; Pickard, Derek; Geue, Lutz
We assessed the ability of a commercial DNA microarray to characterize bovine Shiga toxin–producing Escherichia coli (STEC) isolates and evaluated the results using in silico hybridization of the microarray probes within whole genome sequencing scaffolds. From a total of 69, 954 reactions (393 probes with 178 isolates), 68, 706 (98.2%) gave identical results by DNA microarray and in silico probe hybridization. Results were more congruent when detecting the genoserotype (209 differing results from 19, 758 in total; 1.1%) or antimicrobial resistance genes (AMRGs; 141 of 26, 878; 0.5%) than when detecting virulence-associated genes (VAGs; 876 of 22, 072; 4.0%). Owing to the limited coverage of O-antigens by the microarray, only 37.2% of the isolates could be genoserotyped. However, the microarray proved suitable to rapidly screen bovine STEC strains for the occurrence of high numbers of VAGs and AMRGs and is suitable for molecular surveillance workflows.